Efektivitas Tanaman Lemna (Lemna perpusilla Torr) Sebagai Agen Fitoremediasi Pada Keramba Jaring Apung (KJA) Disekitar Tanjungmas Semarang - U, Umarudin; Nur, Jumriah; Wulandari, Ayu; Izzati, Munifatul (Bioma : Berkala Ilmiah Biologi, 2015)
The port of Tanjung Emas, Semarang as the main port in Central Java that have activity increases pollution impact. Hence the need for special attention and handling by using aquatic plants Lemna perpusilla. The purpose of this research is to know the physical condition of floating around the net keramba Tanjungmas city of Semarang. Designing the application fitoremediasi on floating around the net keramba Tanjungmas city of Semarang and Knowing the prospects of development of fitoremidiasi. This paper uses a case study research methods (case study), which this method has the goal to provide a detailed description of the background, traits and characters typical of cases of water are there in KJA around the Tanjugmas City of Semarang by taking the research object. While this research is the observation and interview is open ended. So that the data obtained indicate that the physical condition of floating around the net keramba Tanjungmas Semarang blackened water greenish colours, smells, and oily. Application design fitoremidiasi by Lemna perpusilla utilize water plants and fish seed banding continued with the observed results. As well as direct application on the KJA in the waters of Tanjung Mas with lemna and seed density setting fish whitefish. Fitoremidiasi development prospects by looking at opportunities to fish bandeng and Lemna perpusilla. Key words: Fitoremediasi, KJA, Fish Bandeng, Lemna perpusilla, Pollution. Â